Stable DHLA–PEG capped PbS quantum dots: from synthesis to near-infrared biomedical imaging - Zamberlan, F.; Turyanska, L.; Patanè, A.; Liu, Z.; Williams, H.E.L.; Fay, M.W.; Clarke, P.A.; Imamura, Y.; Jin, T.; Bradshaw, T.D.; Thomas, N.R.; Grabowska, A.M. (Royal Society of Chemistry, 2018)
The short shelf-life of water-soluble quantum dots (QDs) due to colloidal instability represents a major drawback to their exploitation. This work examines the colloidal stability of PbS nanoparticles capped with dihydrolipoic acid–polyethylene glycol (DHLA–PEG) ligands terminated with functional groups such as –NH 2 , –COOH, OMe and –N3 and their application for in vivo imaging. We prove a mechanism of colloidal instability and develop a strategy to produce for the first time stable PEG-capped PbS quantum dots with high quantum yield and optical emission in the first and the second near-infrared (NIR) windows of low absorption of biological tissues. The NIR imaging of in vivo biodistribution is demonstrated at wavelengths 4 1000 nm, with benefits of reduced tissue absorption and light scattering. The stability, biocompatibility and potential for further QD functionalization open up realistic prospects for non-invasive bioimaging applications.